Acute Monoplegia Due to Spinal Injury - Birua, Gyani Jail Singh (Indian Journal of Neurosurgery, 2019)
Monoplegia due to spinal cord infarction, spinal epidural anesthesia, and epidural blood patch have been reported. Monoplegia due to cervical cord injuries is rare, and monoplegia of upper extremity is even rarer. The authors present a case of a 33-year-old woman, who fell from a two-storey building and developed monoplegia of right upper extremity. Magnetic resonance imaging of the cervical spine reveals long-segment T2W hyperintensity (C3–C7) with involvement of the right hemicord at C4–C5 level.
Keywords: monoplegia; spinal trauma; corticospinal tract injury